2023
DOI: 10.3390/v15030732
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Protein Expression Is Correlated with Shorter Overall Survival in Breast Cancer Patients: A Cohort Study

Abstract: Background: Human cytomegalovirus (HCMV) is increasingly suggested to be involved in human carcinogenesis and onco-modulation due to its ability to contribute to all hallmarks of cancer. Growing evidence demonstrates a link between HCMV infection and various malignancies, including breast cancer, which incidence and mortality are still on the rise. The etiology of breast cancer remains mostly unclear, leaving 80% of breast cancer cases considered to be sporadic. Identifying novel risk- and prognostic factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…An adverse effect of CMV was also noted elsewhere regarding the same pathology [76]. Furthermore, viral protein expression was found to relate to shorter overall survival in patients with breast cancer [77]; CMV IE2 gene expression was also associated with this tumor [78]. In a recent study by Paradowska and colleagues, a significant proportion (70%) of epithelial ovarian cancers (EOC) contained CMV DNA; moreover, the pathogen was significantly more prevalent in EOC than in benign tumors [79].…”
Section: Arguments In Favor Of CMV Oncogenesismentioning
confidence: 89%
“…An adverse effect of CMV was also noted elsewhere regarding the same pathology [76]. Furthermore, viral protein expression was found to relate to shorter overall survival in patients with breast cancer [77]; CMV IE2 gene expression was also associated with this tumor [78]. In a recent study by Paradowska and colleagues, a significant proportion (70%) of epithelial ovarian cancers (EOC) contained CMV DNA; moreover, the pathogen was significantly more prevalent in EOC than in benign tumors [79].…”
Section: Arguments In Favor Of CMV Oncogenesismentioning
confidence: 89%
“…reported in 2 studies higher prevalence of HCMV IE DNA and protein expression in CRC and breast cancer and their metastases to the brain with poor outcome [ 30 , 31 ]. Recently, two studies reported that HCMV gB DNA detection or expression of HCMV IE in breast cancer was found to be associated with shorter survival [ 32 , 33 ]. HCMV IE and E proteins were always detected in the cytoplasm in this study.…”
Section: Discussionmentioning
confidence: 99%
“…An adverse effect of CMV was also noted elsewhere regarding the same pathology [76]. Furthermore, viral protein expression was found to relate with shorter overall survival in patients with breast cancer [77]; CMV IE2 gene expression was also associated with this tumor [78]. In a recent study by Paradowska and colleagues, a significant proportion (70%) of epithelial ovarian cancers (EOC) contained CMV DNA; moreover, the pathogen was significantly more prevalent in EOC than benign tumors [79].…”
Section: Arguments In Favor Of CMV Oncogenesismentioning
confidence: 90%